Miejsce bibliotek w erze transformacji prasy - Felińska, Renata (Biblioteka w chmurze czy chmury nad biblioteką, 2018)
Journals of high, medium and low input consist significant par t of library collection. They play also an important role in formation of society's culture. Press is not the basic source of knowledge and information, but as Polish Studies on Reading (PSR) indicates, for majority of readers, it the most valuable resource of content. Values such as professionalism, honesty, authority, reliability and intelligence are associated with the image of press. For many readers digital version of press becomes more attractive form of expression. More and more titles that traditionally were issued in paper form, now are digitalized. Report from PSR studies shows growth of interest in reading digital press. At the same time these studies show that their range of influence should grow. Report about diagnosis of reader’s behaviors in relation to press does not show optimist vision for sharing press in libraries. However, both analyst’s and librarians’ observations of publishing market give hope that for many years to come printed press will source of knowledge and social opinion. Libraries also have the ability to offer digital press that readers find interesting.